The Effect of Valgus Knee Bracing on Adduction Moment, Pain, and Physical Function in Older Adults with Medial Compartment Knee Osteoarthritis: A 12-months Follow-Up Study - Jamehbozorgi, Ali asghar; Rezaei, Mehdi (Journal of Clinical Physiotherapy Research, 2023)
Introduction: Knee osteoarthritis (OA) is a leading cause of disability in the medial compartment of knee, where increased knee adduction moment (KAM) exacerbates disease progression. Valgus knee bracing is a non-surgical intervention aimed to reducing KAM, alleviating pain, and improving function . Material and Methods: This single-group intervention pre and posttest design study aimed to evaluate the effectiveness of valgus knee bracing over a 12 months follow-up period on adduction moment, pain, and physical function in older with medial compartments OA. Twenty-one patients with grade 2 or 3 medial knee OA were enrolled. All participants used a valgus knee brace for 12 months. KAM, pain, satisfaction and functional performance were assessed at baseline and 12 months. Results: Significant reductions in KAM (28%, P=0.02) and pain (25%, P=0.00) were observed after 12 months of using valgus knee bracing. Functional improvement was also significant (41%, P=0.005). Patient satisfaction showed a 9% increase (P=0.078) too. Conclusion: Valgus knee bracing significantly reduces KAM and pain while improving motor function in patients with medial compartment knee OA. However, patient satisfaction was moderate which indicate that its need improvement comfort in brace design. These findings highlight the potential of valgus bracing to delay the need for surgical intervention, offering a conservative treatment option for managing knee OA. Keywords: Osteoarthritis, Knee, Orthotic Devices, Biomechanical Phenomena, Pain, Physical Functional Performance, Patient Satisfaction